The association of sociodemographic and objectively-assessed disease variables with fatigue in systemic sclerosis: an analysis of 785 Canadian Scleroderma Research Group Registry patients. Issue 2 (February 2017) - Levis, Brooke; Kwakkenbos, Linda; Hudson, Marie; Baron, Murray; Thombs, Brett
Abstract Fatigue is prevalent among patients with systemic sclerosis (SSc). To date, studies investigating fatigue in SSc have been hampered by the instruments used to measure fatigue in SSc and have included patient-reported rather than objectively-rated measures of disease. The Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) scale is a validated measure for assessing fatigue in SSc that, compared to other instruments, provides good coverage of the full range of the fatigue spectrum. The objective of this study was to assess sociodemographic and objectively-rated disease-related associates of fatigue, as measured by the FACIT-F, in a large sample of patients with SSc. Fatigue was assessed using the FACIT-F scale. Disease severity was assessed using Medsger's severity scale. Multivariable linear regression was performed to assess the independent associations between sociodemographic and medical variables and fatigue. Among 785 patients, the mean FACIT-F score was 32.2 (SD = 12.1). Being age 40–49 (reference = 60+; standardized regression coefficient (β ) = −0.11), less than post-secondary education (β = 0.07), having more medical comorbidities (β = −0.11) and more severe muscle (β = −0.10), gastrointestinal (β = −0.15), lung (β = −0.13), and general system disease severity (β = −0.13) were independently associated with more fatigue (p < 0.05). Fatigue in SSc was independently associated with more severe disease. These data contribute to a better understanding of fatigue in SSc and help inform patient-centered research in SSc.